Penyelidikan dalam pendidikan Islam : permasalahan reka bentuk dan metodologi - Hashim, Rosnani (Yayasan Takmir, 2010)
Research design and methods are essential before any form of research can be conducted. A proper research design and an accurate research method are important to ensure that the findings are valid and reliable. Weaknesses in the research method might not yield accurate findings. Both research design and research method are underlined by epistemological grounds. This article examines problems related to research design and methods in Islamic education. It examines the weaknesses of research in Islamic education that has not been producing findings that could benefit teachers, policy makers and students.